DESIGNING AN ANDROID-BASED EMPLOYEE INDIVIDUAL ASSISTANT APPLICATION (ASIKA) (CASE STUDY: AT MADTIVE STUDIO) - Nugraha Pratama, Agie Nugraha (Teknik Informatika Universitas Suryakancana Cianjur, 2025)
This research is based on the process and analysis conducted at one of the software houses in Cianjur district named Madtive Studio. Madtive Studio is a software house engaged in Information Technology, Systems and Branding which was established in 2015. The main focus of this company is the development of application systems for all types of companies ranging from retail, services, distributors and manufactures. This is done in order to become a benchmark for the author in carrying out research. The author found 3 factors as follows: (1) Input and reporting of data still use conventional methods. (2) Confusion when controlling work. (3) Difficulty in reporting work. For this reason, a HR management program is needed so that the ongoing procedures are well-systematic and will make it easier for owners and employees to input and report data. Making the system usually begins with an analysis process, but the process of gathering system requirements is not always found in the analysis process. In this study, the system design that the author uses is the extreme programming (XP) method. Method (XP) is needed to design a system that will be made by taking into account the needs and desires of users. In (XP) feedback from users becomes one of the important values. The result of the research is a system design with only one display, which is based on Android with a firebase database. This will make the user more simple but useful